Circumcision with Intravenous (IV) Ketamine, Thiopentone and Penile Block: A Safe and Cost-effective Anesthetic Technique (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Circumcision is a common minor surgical procedure among Muslim and Jews population. Both surgeon and guardian want safe but low-cost anesthesia for this procedure. Sometimes parents do not agree to anesthetize their child for this purpose. Using penile block with IV ketamine and thiopentone sodium (TPS), patients can be managed smoothly without any major complication and it is a cost-effective technique.Objective: This study was designed to perform safe and cost-effective anesthetic management for circumcision of children.Materials and Methods: This is an observational prospective study carried out in Dhaka Shishu Hospital and Dhaka Central Hospital during the period of January to December 2011. Total 336 cases of circumcision were done. Children with American Society of Anesthesiologists (ASA) Grades I & II, between 1 and 12 years of age were selected for this study. Patient was sedated using Ketamine 1 mg/kg plus TPS 2.5 mg/kg. Then penile block was given. Close observation and monitoring was done clinically as well as with the help of pulse oximeter and sphygmomanometer.Results: Among 336 patients no cases of laryngospasm, cynanosis, vomiting and convulsion was observed. Cough developed in 7 cases, slight fall of SpO2 in 10 cases and subcutaneous hematoma in 11 cases were noted. Incomplete block occurred in 5 cases, urethral puncture in cases and accidental injection in corpus cavernosum in 2 cases. Approximate average total cost for anesthesia procedure per case was 3.5 USD only.Conclusion: Circumcision with low dose intravenous Ketamine and TPS with penile block is a safe and cost-effective anesthetic technique.DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.24Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 34-37